HUBUNGAN ANTARA TINGKAT STRES DENGAN SIKLUS MENSTRUASI PADA MAHASISWI TINGKAT II A AKADEMI KEPERAWATAN PANTI KOSALA SURAKARTA - Lilik Sriwiyati; Tyas Puspitasari (KOSALA : Jurnal Ilmu Kesehatan, 2017)
Stress is any situation where the nonspecific demands requires an individual to respondor take action. Stress can affect the menstrual cycle, because in times of stress, thehormone cortisol as a product of glukokortiroid adrenal cortex may affect the amount ofprogesterone in the body. Purpose of this research is to seek the relation between stresslevel with menstrual cycle on student level II A in Panti Kosala Nursing Academi.Subjects of this research were the student level II A in Panti Kosala Nursing Academi.The samples were 30 respondents selected by using purposive sampling method.Method of the research is a corelational study. This research has two variables, theindependent variable is stress level and the dependent variable is menstrual cycle.Collecting data use questionnaire paper. Data analysis use Chi Quadrat Test withp=0.05.Results of this research are shown that there were 11 respondents who have a mildstress, 5 people as normal menstrual cycles, 4 people as polymenorhea and 2 people asoligomenorrhea. Respondents who have average stress about 18 people, 13 people asnormal menstrual cycles and 5 people as oligomenorrhea. While respondents who havesevere stress as much as one person with the menstrual cycle is oligomenorrhea.Statistical test use Chi Quadrat with the result p = 0.031.The Conclusion of this research is that there is a relation between stress level with themenstrual cycle on student level II A in Panti Kosala Nursing Academi.Keywords: stress level, menstrual cycles